2008
DOI: 10.1001/jama.2008.827
|View full text |Cite
|
Sign up to set email alerts
|

Has This Prepubertal Girl Been Sexually Abused?

Abstract: Vaginal discharge as well as posterior hymenal transections, deep notches, and perforations raise the suspicion for sexual abuse in a prepubertal girl, but the findings do not independently confirm the diagnosis. Given the broad 95% confidence intervals around the likelihood ratios for the presence of findings along with the low or unknown sensitivity of all physical examination findings evaluated, the physical examination cannot independently confirm or exclude nonacute sexual abuse as the cause of genital tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 36 publications
0
20
0
5
Order By: Relevance
“…Furthermore, the diagnostic accuracy of markers was not always estimated, the analysis being limited to estimating the association between a marker and maltreatment. Similarly, diagnostic accuracy of genital examination for identifying sexually abused prepubertal girls was reviewed [10], but tools only identified children who were victims of a severe form of sexual abuse (genital contact with penetration). Furthermore, the sensitivity for several potential markers, such as hymeneal transections, deep notches or perforations, was never reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the diagnostic accuracy of markers was not always estimated, the analysis being limited to estimating the association between a marker and maltreatment. Similarly, diagnostic accuracy of genital examination for identifying sexually abused prepubertal girls was reviewed [10], but tools only identified children who were victims of a severe form of sexual abuse (genital contact with penetration). Furthermore, the sensitivity for several potential markers, such as hymeneal transections, deep notches or perforations, was never reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 12% to 25% of girls and 8% to 10% of boys suffer some form of sexual abuse up to 18 years of age 3 . Girls are at greater risk of facing the problem, while boys are more likely to hide its occurrence 4 . The author of the sexual violence is generally known to the child and close family, sometimes responsible for its protection, often an expressive number of cases are performed by the biological father, grandfather or stepfather 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Berkoff et al, in their systematic review of the literature on sexual abuse of prepubertal girls, published in 2008, found only 11 articles that were suitable for inclusion (31). Their conclusions were as follows:…”
Section: The State Of the Evidence Regarding The Sexual Abuse Of Chilmentioning
confidence: 99%